On the Use of Quantitative Methods in Accounting Research in Poland - Marek Gruszczyński (Journal of Banking and Financial Economics)
This paper presents a review of published accounting research based on quantitative methods originating in Poland between 2010 and 2021. Twenty-one international and national journals were examined, all having “accounting” in their title, as well as the leading Polish journal on accounting research – Zeszyty Teoretyczne Rachunkowości (ZTR, Theoretical Journal of Accounting). The principal finding is that Polish authors – especially those using quantitative methods – rarely publish in top accounting journals outside of Poland. They most frequently publish quantitative papers in ZTR, although those papers account for just 5% of the total number of papers published there. The corresponding percentage of quantitative papers is much higher in leading international accounting journals. This paper is presented as a voice in the debate within Polish academia on the development of the accounting discipline.